(untitled) (Social and Environmental Law Journal, 2024)
Food Sovereignty should be associated with the guarantee of the Human Right to Adequate Food (HRAF) and Food and Nutritional Security (FNS). The first concept relates to the right of peoples to decide what is produced and consumed, while FNS emphasizes the right to permanent access to quality food in sufficient quantities on a continuous basis. HRAF is the inherent right of individuals to regular and unrestricted access to safe and healthy food, in adequate and sufficient quantities, without interruption, and in respect of their culture. This study aims to elucidate and describe the Brazilian food system, its relationship with the consequences generated by the global syndemic, and how this phenomenon affects, through the racialized segment, the HRAF of Traditional Communities, with a focus on the Kalunga in the state of Goiás. Document research and a diagnostic survey were conducted in the Kalunga Congonhas Community. Changes in the traditional eating habits of the Community were observed, and the concepts of Food Sovereignty, Adequate Food, and Food and Nutritional Security are complementary and highly related to the guarantee of the Human Rights of the Kalunga People.